Tetrazoles Leitmotif: An Intriguing Insight into Contemporary Developments and Biological Activities - Mohite, Popat; Nahar, Deepali; Lonkar, Ankita; Kadam, Aditya; Desle, Kaustubh (Anti-Infective Agents, 2024)
Heterocyclic compounds with a tetrazole core are of great interest because they represent an important class of synthetic compounds with a wide range of relevant biological properties that have the potential to be clinically translated as treatments for a variety of disorders. Due to their beneficial bioactivities, heterocycles with a tetrazole scaffold have the interest of organic and medicinal chemists and sparked much attention in recent years. Tetrazoles are a form of nitrogen heterocycle found in several natural compounds in addition to their pharmacologically active nucleus. The tetrazole ring is similar to carboxylic acids and acts as a bioisostere analogue. A booster is a set of molecules with identical physiological features, including biological activity. Tetrazole nuclei are found in compounds used to evaluate new antimicrobial, anticancer, antitubercular, anticonvulsant, antimalarial, antihypertensive, and anti-inflammatory medicines. Tetrazole and its derivatives' broad and potent actions have established them as pharmacologically significant scaffolds. So far, tetrazole ring alterations have proven to be highly efficient, with greater efficacy. This review aims to provide an in-depth recapitulation of recent trends used to synthesize promising Tetrazole incorporated compounds and focus on the clinical significance of functionalized tetrazole analogues, which would essentially aid medicinal chemists in new research exploration and discovery in this field.
Keywords: anti-inflammatory medicines